Inclusion as Assimilation, Integration, or Co-optation? A Post-Structural Analysis of Inclusion as Produced Through Mental Health Research on Peer Support. (May 2023) - Sinclair, Aimee; Gillieatt, Sue; Fernandes, Christina; Mahboub, Lyn
In the last 20 years, research on the inclusion of peer support within mental health settings has burgeoned, paralleling the broad adoption of service user inclusion within policy as a moral imperative and universally beneficial. Despite the seemingly progressive impetus behind inclusion, increasingly peer support workers talk of exhaustion working within mental health systems, the slow rate of change to oppressive values and practices, and ongoing experiences of workplace exclusion. Such experiences suggest differences in the way in which inclusion is produced across different stakeholder groups and contexts. In this article, we adopt Bacchi's 'what's the problem represented to be?' approach to identify how mental health research, often understood as an a-political activity, produces versions of inclusion. We argue current research predominantly produces inclusion as 'assimilation' and 'integration'. We use critical inclusion, mental health, and survivor scholarship to evaluate the effects these productions have for peer support and peer support workers, finding that both problematise peer support workers and those seeking support. We consider possibilities for more liberatory productions of inclusion, building on the notion of inclusion as 'co-optation'. Our analysis points to the need for researchers to engage with an uncomfortable reflexivity to enable more emancipatory possibilities regarding inclusion and peer support.